Ways to Use Photoshop to Make A Positive Contribution to Environmental Protection - Ren, Xinling (International Journal of Computer Science and Information Technology, 2024)
This article through the Photoshop to protect the environment works production, hope to improve everyone's environmental protection consciousness, stimulate students' interest in learning, help teachers to teach. The basic operations used in the work are layer style, highlight, layer mask, brush tool, cropping tool, invert, torus, filter, channel, decolorization, opacity, etc. Simple and easy to understand, the meaning of the work is clear at a glance.This paper first introduces some basic knowledge of Photoshop software, such as Photoshop overview, Photoshop software introduction, the origin and development of Photoshop, the second chapter introduces the general steps of Photoshop production, such as determining the teaching goal, selecting the appropriate teaching content and design, etc. The next chapter describes the production steps and skills of Photoshop environmental protection works in detail, including the preparation of materials and the specific production process of works; The fourth chapter mainly introduces the experience in the production process; The fifth chapter introduces the application prospect of Photoshop and the evaluation of Photoshop software and works.